SURVEY ON CIVITAS ACADEMICA AND STAKEHOLDERS' UNDERSTANDING TOWARDS POLIMEDIA'S VISION, MISSIONS, GOALS, AND OBJECTIVES - Suratni Suratni; Yuyun Khairunisa; Henra Nanang Sukma; Refi Yuliana; Yudha Pradana; Putri Surya Cempaka; Dodik Catur Pramudiono (Jurnal Ilmiah Publipreneur, 2021)
P4MP plays a role in assisting the Director in ensuring the quality of education at Politeknik Negeri Media Kreatif. In carrying out this role, P4MP conducted an understanding survey of the academic community and stakeholders towards Polimedia's Vision, Mission, Objectives and Strategy (VMTS). This survey aimed to measure the level of knowledge and understanding of lecturers, staffs, students, functional and structural officials of VMTS Polimedia. Researchers used a quantitative method with purposive random sampling. Based on the data, it is known that 96.9% of lecturers knew and 87.8% of lecturers understood VMTS Polimedia. Furthermore, 96.1% of the respondents knew and 84.3% of the respondents understood the Polimedia VMTS. For college-students, as many as 73.86% of students knew and 62.2% of students understood the meaning of VMTS Polimedia. Respondents know VMTS Polimedia from 45.6% Polimedia website, 25.3% Polimedia social media, 17% bulletin boards on campus, 7.4% academic rule books, and 4.7% from other media.